1995
DOI: 10.1038/jcbfm.1995.2
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of the Rates of the TCA Cycle, Glucose Utilization, α-Ketoglutarate/Glutamate Exchange, and Glutamine Synthesis in Human Brain by NMR

Abstract: Summary: 13C isotopic tracer data previously obtained by 13C nuclear magnetic resonance in the human brain in vivo were analyzed using a mathematical model to deter mine metabolic rates in a region of the human neocortex. The tricarboxylic acid (TCA) cycle rate was 0.73 ± 0.19 fLmol min -I g-I (mean ± SD; n = 4). The standard deviation reflects primarily intersubject variation, since individual uncertainties were low. The rate of a-ketoglu tarate/glutamate exchange was 57 ± 26 fLmol min -1 g -1 (n = 3), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
319
2
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(345 citation statements)
references
References 49 publications
23
319
2
1
Order By: Relevance
“…181 13C MRS is an even more powerful technique to measure glutamate activity in the brain and offers a means of capturing dynamic metabolite flux rates of glutamate. 182,183 This technique offers the possibility of monitoring dynamic changes in the glutamate/glutamine shuttle between astrocytes and neurons in discrete brain regions, and it could be an excellent method for monitoring the effects of glutamatergic modulating drugs for mood and anxiety disorders.…”
Section: Neuroimaging Of Glutamatergic Function In Anxiety Disordersmentioning
confidence: 99%
“…181 13C MRS is an even more powerful technique to measure glutamate activity in the brain and offers a means of capturing dynamic metabolite flux rates of glutamate. 182,183 This technique offers the possibility of monitoring dynamic changes in the glutamate/glutamine shuttle between astrocytes and neurons in discrete brain regions, and it could be an excellent method for monitoring the effects of glutamatergic modulating drugs for mood and anxiety disorders.…”
Section: Neuroimaging Of Glutamatergic Function In Anxiety Disordersmentioning
confidence: 99%
“…Although the ground work for all 13 C MRS was established by chemists, physical chemists and physicists over many years, we owe almost all of the translational research which made it possible to perform simpler 13 C NMR experiments in whole-body NMR instruments at relatively low magnetic fields (1.5, 2.1, 4.1 T) to a small number of laboratories, [4][5][6][7][8][9] particularly at the University of Zurich, Switzerland and Yale University, USA. The move to higher fields has also proceeded only slowly, and has so far largely been confined to normal volunteers.…”
Section: History Of Clinical 13 C Mrsmentioning
confidence: 99%
“…Lactate, readily detected by 1 H MRS but at a concentration of only 2-3 mM in this patient, was not observed with natural abundance 13 C MRS patient positioning needed for accurate spectral subtractions. 10 Others have experimented with localization and the consequent narrower 13 C-excitation range, 6,7,9 thereby avoiding difference-spectroscopy. However, the localization scheme itself (ISIS) is a difference method and shares some of the disadvantages.…”
Section: Proton-decoupling Safety and Noementioning
confidence: 99%
“…The time course of label incorporation into 4-13 C glutamate yields (with appropriate corrections for the delays in labeling introduced by the small intervening lactate and glycolytic intermediate pools) the rate of the neuronal TCA cycle. 27 After formation in the neuron 4-13 C glutamate may be released from the nerve terminal and taken up by surrounding glial cells, which are often referred to as astrocytes based upon their morphology. In the glia the glutamate will be converted by glutamine synthetase into 4-13 C glutamine.…”
Section: Mrs Studies Of Neuronal Glial Gluta-mate Traffickingmentioning
confidence: 99%
“…[17][18][19]28,33 In 1994 it was first demonstrated that in vivo 13 C NMR may be used to measure the rate of glutamine labeling from 1-13 C glucose in human occipital/parietal cortex. 18,27 However the rate of the glutamate/glutamine cycle was not uniquely determined from these first experiments due to the inability to distinguish the glutamate/glutamine cycle from other sources of glutamine labeling in the glia. The studies in rats by Sibson and coworkers 29,30 allowed a constraint to be placed on the maximum flow of label from glial pyruvate dehydrogenase into glutamine as the rate of anaplerosis.…”
Section: Mrs Studies Of Neuronal Glial Gluta-mate Traffickingmentioning
confidence: 99%